2018
DOI: 10.1111/1742-6723.12873
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with suspected chronic digoxin toxicity: A comparison of clinical characteristics of patients receiving and not receiving digoxin‐Fab

Abstract: Digoxin-Fab was more commonly administered when heart rate was <51/min. It had a small effect on increasing heart rate; however, individual response to digoxin-Fab was variable as patients were using other negative chronotropic medications. In symptomatic bradycardic patients on multiple heart failure medications, positive chronotropic and potassium-lowering therapies should be considered in concert with digoxin-Fab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
8
1
2
Order By: Relevance
“…There are several studies reporting the effect of cardenolides in heart diseases (Campbell and Mc Donald 2003;Biteker et al 2017;Gurel et al 2017), but evaluation of these compounds to treat VL is lacking. Although cardenolides have been reported as toxic compounds (Hauptman et al 2016;Arbabian et al 2018), the low doses of either DIGI on its free form or incorporated into a micellar composition (DIGI/Mic) tested in our study did not induce any significant toxicity when used to treat the infected hosts. Conversely, infected animals receiving miltefosine did present with toxicity.…”
Section: Discussioncontrasting
confidence: 50%
“…There are several studies reporting the effect of cardenolides in heart diseases (Campbell and Mc Donald 2003;Biteker et al 2017;Gurel et al 2017), but evaluation of these compounds to treat VL is lacking. Although cardenolides have been reported as toxic compounds (Hauptman et al 2016;Arbabian et al 2018), the low doses of either DIGI on its free form or incorporated into a micellar composition (DIGI/Mic) tested in our study did not induce any significant toxicity when used to treat the infected hosts. Conversely, infected animals receiving miltefosine did present with toxicity.…”
Section: Discussioncontrasting
confidence: 50%
“…Most patients that present with digoxin toxicity are elderly, have other cardiac and noncardiac comorbidities, and take multiple medications including those known to potentially interfere with serum digoxin concentrations (SDC) [12]. The most common presentation of digoxin toxicity is due to unintentional overdose or decreased drug clearance due to hepatic or renal dysfunction, as opposed to acute, intentional ingestions [2,6,12]. Most patients with acute toxicity present with anorexia, nausea, emesis, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Visual changes such as halos, scotomas, flashing lights, and xanthopsia may also be reported [2,11]. Historically, bradycardia has been associated with digoxin toxicity, but recent studies have suggested that bradycardia in the setting of digoxin toxicity is more likely multifactorial and minimally improves with treatment [6,11]. Renal failure is the most common precipitating event to digoxin toxicity causing decreased drug clearance, and is associated with worse outcomes when concurrent hyperkalemia and ventricular arrhythmias are present, as in our patient [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear to what extent digoxin accounts for clinical features manifested by patients with an elevated digoxin concentration. Elevated digoxin concentrations are expected in patients who have multiple organ failure from any cause [7]. In a previous study, we showed that 1-2 vials of digoxin-specific Fab (digoxin-Fab) in patients with chronic digoxin poisoning rapidly led to zero free serum digoxin concentrations; but had only a modest effect on heart rate and no effect on blood pressure or other features [8,9].…”
Section: Introductionmentioning
confidence: 91%